2017
DOI: 10.1387/ijdb.170012ts
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the aortic wall by coelomic lining-derived mesenchymal cells accompanies the onset of aortic hematopoiesis

Abstract: In vertebrates, definitive hematopoietic stem cells (HSCs) first emerge in the ventral wall of the aorta in the Aorta-Gonad-Mesonephros (AGM) region of the embryo, where they differentiate from a specialized type of endothelium termed Hemogenic Endothelium (HE). While the transition from HE to hematopoietic tissue has received much experimental attention, much less is known regarding generation of HE itself. The current study investigates the emergence of the HE in the chick embryo aorta. Using the HE marker R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…Therefore, we next transplanted PK8 cells with or without CAFs onto CAM samples and found that vessel formation in the PK8 + CAF group was much more intense than that in the PK8 cell-only group (Figure 4G). Moreover, we used an antibody against the highly specific endothelial marker VE-cadherin to label the vessels on CAM samples 24 and found that VE-cadherin was upregulated in the PK8 + CAF group compared with the PK8 cell-only group, further supporting our previous data (Figure 4H). These findings suggested that angiogenesis is maintained by vegfa originating from CAFs in the tumor microenvironment.…”
Section: -Pgdh Depletion In a Highly Fibrotic Tumor Microenvironment ...supporting
confidence: 88%
“…Therefore, we next transplanted PK8 cells with or without CAFs onto CAM samples and found that vessel formation in the PK8 + CAF group was much more intense than that in the PK8 cell-only group (Figure 4G). Moreover, we used an antibody against the highly specific endothelial marker VE-cadherin to label the vessels on CAM samples 24 and found that VE-cadherin was upregulated in the PK8 + CAF group compared with the PK8 cell-only group, further supporting our previous data (Figure 4H). These findings suggested that angiogenesis is maintained by vegfa originating from CAFs in the tumor microenvironment.…”
Section: -Pgdh Depletion In a Highly Fibrotic Tumor Microenvironment ...supporting
confidence: 88%
“…The coelomic epithelium lines the embryonic body cavity, or coelom, in vertebrates and many other animal species. During vertebrate development, the coelomic epithelia on the two lateral sides of the embryo converge medially to generate the dorsal mesentery (DM), which suspends the gut tube in the body cavity and which normally becomes located in the embryonic midline (Arraf et al, 2017(Arraf et al, , 2016. A previous study (Arraf et al, 2016) reported that positioning of the DM is a dynamic process that depends on the rates of coelomic epithelium convergence on the two sides of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Following secondary antibody incubation, embryos were washed with 0.3% triton X-100 in PBS and then three washes are done with PBS. The following primary antibodies were used: mouse anti-GFP (1:500, Molecular Probes 3E6) and rabbit VE-Cadherin (1:500) (Arraf et al, 2017). Secondary antibodies used were Alexa488 and Cy3(1:250, Jackson ImmunoResearch).…”
Section: Electroporationmentioning
confidence: 99%